Schoolscapes in Multicultural Centers in Finland : How Staff Members Perceive Multilingualism - Ishimoto, Marino (2020)
This study aims at exploring how multilingualism is represented in multicultural centers in Finland, and interpretations of these representations made by the staff members in multicultural centers through the lens of schoolscape. To accomplish the study aims, walking interviews with staff members was conducted in five different multicultural centers. The fragments of schoolscape in the multicultural centers were photographed. Discourse analysis was used for analyzing excerpts from the interviews. The findings reveal the covert language policy towards multilingualism in the investigated multicultural centers, which was to use Finnish as a lingua franca, while other languages than Finnish were used accordingly. Varieties of interpretation towards this covert language policy were made by the staff members. Some of them rather encouraged immigrants to speak Finnish, while others also pointed out the positive aspects of speaking immigrants’ mother tongue. Additionally, a perceived lower status of the Swedish in the multicultural center came to fore, even though Swedish is the other national language in Finland. Fragments of schoolscape in Finnish were carefully designed to make them understandable regardless of the Finnish language proficiency. With the findings, language policy and ideology inside and outside of the multicultural centers are reflected. The ways to enhance multilingualism in the aspect of the dichotomy in the use of language, time restrictions, staff members’ awareness of the impacts of the schoolscape on multilingualism are suggested. The number of participants, researchers’ Finnish language proficiency and focusing only on the visual aspect of schoolscape may limit the findings.